Justice for victims: An analysis of child sexual assault through the lens of gustav radbruch's legal values at the Luwuk District Court - Abdan Syakura; Yuliati Yuliati; Syahrul Machmud (Journal of Law Science, 2024)
This study conducts an analysis of two judicial decisions pertaining to sexual offenses against minors: Verdict Number 2/Pid.Sus-Anak/2025/PN Luwuk, which involves a juvenile offender, and Verdict Number 37/Pid.Sus/2025/PN Luwuk, which pertains to an adult offender. A normative juridical approach was utilized, informed by Gustav Radbruch’s theory of law and Lawrence Friedman’s legal system theory. The findings indicate a differentiated legal response contingent upon the status of the offender. In the case of the juvenile, the court rendered a conditional sentence that adopted a rehabilitative strategy, thereby reflecting principles of restorative justice and prioritizing the best interests of the child. In contrast, the adult offender received a prison sentence accompanied by a maximum fine, devoid of leniency, which underscores a stringent protective stance towards the child victim and serves as a deterrent for society. Both rulings exemplify the effective operation of legal frameworks and indicate advancements in Indonesia’s legal culture concerning the firm and equitable handling of sexual violence against children. This study emphasizes the necessity of balancing justice, legal certainty, and social utility within the criminal justice system for both juvenile and adult offenders.